A study on the manpower issues and productivity in warehouse and distribution centres in Singapore - Ang, Johnnie Yue Jun (2014)
Productivity plays a crucial role in keeping Singapore competitive economically and at a leading edge globally. However, productivity growth has been a major concern for the Singapore government, with it being negative in 2012, and was zero growth in 2013. Thus, the government has come up with various schemes to help companies in an effort to raise productivity.